The Influence of Digital Marketing, Online Customer Reviews and Millennial Culture on Purchase Decisions on Gacoan Noodles (Study on Gacoan Noodle Consumers Mojokerto Branch) - Rohmawati Nur Khasanah; Evi Fitrotun Najiah; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2024)
This research aims to determine the effect of free shipping, trust and online customer reviews on purchasing decisions on e-commerce shopee in tambakrigadung village. This type of research is quantitative research. The population in this study are customerse who shop online through shopee in tambakrigadung village. The sampling techniqueused a purprosive sampling method using the slovin formula to obtain a sample size of 100 respondents. The data collection technique uses online questionnaire distribution via google form which has been tested for validity and reliability. Data analysis technique use classical assumption tests, multiple linier regression, coefficient of determination, t test and f test using spss 26. This research starts from november 2023 to march 2024. The results of this research state that the free shipping variable has a value of 0.002 < 0.050 while the calculated t value is 3.215 > t table (1.98498), the trust variable has a value of 0.000 < 0.050 while the calculated t value is 4.842 > t table (1 .98498), the online customer review variable has a value of 0.000 < 0.050 while the calculated t value is 5.258 > t table (1.98498), so H1 is accepted so it can be concluded that the free shipping, trust and online customer review variables partially influence purchasing decisions on e-commerce Shopee in Tambakrigadung village. From the F test, it shows that the calculated f value > f table is 49.310 > 2.70 with a significance value of 0.000 < 0.050, so H2 is accepted so it can be concluded that the variables free shipping, trust and online customer reviews together or simultaneously influence purchasing decisions on e-commerce Shopee in Tambakrigadung village. The trust variable is the most dominant variable because it has a p value of 0.00 < 0.005 and has the largest value β (0.626) among other variables on purchasing decisions (Y).